The Potential Adoption of IFRS for U.S. Issuers: A Textual Analysis of Responses to the Proposal - Pawsey, Nicholas; Brown, Alistair; Bikram, Chatterjee (Asian Journal of Business and Accounting, 2013)
This paper uses textual analysis to analyse the comments received by the U.S. SEC on the proposal to allow U.S. listed companies to prepare financial statements following International Financial Reporting Standards (IFRS). The paper contributes to the understanding of the overall desirability of international accounting convergence as well as the politics involved in attempting to reach consensus on such decisions. Most respondents supported the proposal. Respondents outlined the advantages of adopting IFRS as enhanced comparability, simplification, cost savings, extensive information sets, its capacity to improve the standard setting process, and its potential to serve U.S. interests. On the other hand, a minority of respondents were not supportive of the proposal. There was criticism of the lack of independence, enforcement mechanisms and resource availability of the IASB; the deleterious effect on U.S. interests; the questionable quality of the IFRS; and the perceived myths of convergence. Following the review of such comments, the paper outlines the implications of such a potential adoption of IFRS in U.S. to the Asian region as the pressure to extend IFRS to non-listed companies mounts. The paper also argues that Asian countries need to lobby for higher representation on the IASB and consider local customs, law and context while adopting IFRS, as such factors have been stressed upon by U.S. respondents to the SEC’s proposal.